2017
DOI: 10.1016/j.electacta.2017.06.096
|View full text |Cite
|
Sign up to set email alerts
|

Improved EIS Analysis of the Electrochemical Behaviour of Carbon Steel in Alkaline Solution

Abstract: 2017-08-25T16:30:20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 21 publications
3
16
0
1
Order By: Relevance
“…EIS is a powerful technique for mechanistic investigations as it can be used to determine several parameters, such as the bulk concrete properties at high frequencies [390][391][392], the mass-transfer phenomena and diffusion coefficients [393][394][395], or the properties of the passive film on the steel surface at low frequencies [90]. In alkaline solutions, it was shown that EIS measurements can provide insight into the mechanism of the cathodic reduction at the oxide layer of carbon steel, allowing characterization of the oxide film [396]. The proposed methodology includes the use of a power-law distribution and a complex capacitance representation of the data when using a CPE for describing the film impedance [396].…”
Section: Measurement In Three-electrode Configurationmentioning
confidence: 99%
“…EIS is a powerful technique for mechanistic investigations as it can be used to determine several parameters, such as the bulk concrete properties at high frequencies [390][391][392], the mass-transfer phenomena and diffusion coefficients [393][394][395], or the properties of the passive film on the steel surface at low frequencies [90]. In alkaline solutions, it was shown that EIS measurements can provide insight into the mechanism of the cathodic reduction at the oxide layer of carbon steel, allowing characterization of the oxide film [396]. The proposed methodology includes the use of a power-law distribution and a complex capacitance representation of the data when using a CPE for describing the film impedance [396].…”
Section: Measurement In Three-electrode Configurationmentioning
confidence: 99%
“…Thus, the graphical method is used in the current work to get a better understanding of the system being investigated. The capacitance of the oxide layer can be accurately extracted from the complex capacitance plane after the correction by removing the solution resistance Rs as following [22]- [26]:…”
Section: Surfaces Electrochemical Characterisationmentioning
confidence: 99%
“…The capacitance of an oxide film can be graphically determined by extrapolating the high frequency real capacitance, Cf ≃ CHF, using the Cole-Cole capacitance representation [52,66,67].…”
Section: Electrochemical Testing Of Hpt-processed Materialsmentioning
confidence: 99%